2003
DOI: 10.1029/2002jd002359
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sampling using an Aerodyne aerosol mass spectrometer 2. Measurements of fine particulate chemical composition in two U.K. cities

Abstract: In part 1 of this series, techniques for generating quantitative information on fine airborne particulate‐size and chemically resolved mass concentration from an Aerodyne aerosol mass spectrometer were introduced. Presented here are the results generated using these techniques from sampling U.K. urban air with such an instrument in Edinburgh during October 2000 and in Manchester during July 2001 and January 2002. Data on the total mass concentrations and size‐resolved mass distributions of nitrate, sulfate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
227
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 214 publications
(254 citation statements)
references
References 50 publications
23
227
1
3
Order By: Relevance
“…This mode was principally composed of organic material with very small concentrations of inorganic species. This finding is consistent with previous observations made at other urban sites in the UK and the US Allan et al, 2003b;Drewnick et al, 2004b). The small organic mode appears to be characteristic of urban sites and fresh emissions.…”
Section: Overview Of Chemical Composition and Size Distributionssupporting
confidence: 83%
See 4 more Smart Citations
“…This mode was principally composed of organic material with very small concentrations of inorganic species. This finding is consistent with previous observations made at other urban sites in the UK and the US Allan et al, 2003b;Drewnick et al, 2004b). The small organic mode appears to be characteristic of urban sites and fresh emissions.…”
Section: Overview Of Chemical Composition and Size Distributionssupporting
confidence: 83%
“…The major source of these trace gases in urban environments is from motor vehicle exhaust (GVRD, 2002), and the strong correlation suggests that combustion-related emissions (with traffic likely representing a large fraction) are the main source of the small organic mode at Slocan Park urban site. This is consistent with many other studies including our previous urban measurements in two major UK cities (Allan et al, 2003b) Experiments performed in our laboratories have shown that mass spectra obtained using the AMS compare well to the NIST standard library of mass spectra for a range of chemical compounds with the exception of di-and poly carboxylic acids and humiclike substances, where m/z 44 (CO 2 + ) was found to be much more pronounced in the AMS spectra. The enhanced m/z 44 signal was coupled with a very strong peak at m/z 18 indicative of H 2 O + , implying thermal breakdown of the carboxylic acid group on the vaporizer.…”
Section: Urban Organic Particulatesupporting
confidence: 78%
See 3 more Smart Citations